The Influence of Information and Communication Technologies on Knowledge Exchange Among Higher Education Students - Odularu, Oluwayemi IbukunOluwa (Journal of Cultural Analysis and Social Change, 2026)
Information and Communication Technologies (ICTs) have transformed knowledge exchange dynamics in higher education, fostering collaborative learning and improved academic performance. However, disparities in access, digital literacy, and institutional support continue to impede equitable participation among students, particularly in developing contexts. The aim of this study is to examine the influence of Information and Communication Technologies (ICTs) on knowledge exchange among higher education students. The review focused on higher education institutions globally, with implications for developing contexts such as South Africa, where ICT integration remains uneven across institutions. A systematic literature review of 85 peer-reviewed studies was conducted using major databases, including Scopus, Web of Science, and ERIC. The analysis was guided by the Technology Acceptance Model (TAM) and Theory of Reasoned Action (TRA), focusing on perceived usefulness, ease of use, and behavioural intention to adopt ICTs for knowledge sharing. Findings reveal that ICTs significantly enhance students' knowledge exchange, promoting interactive and collaborative learning. However, barriers such as, limited user training, inadequate institutional infrastructure, and unreliable technical support persist, hindering effective adoption. The study concludes that while higher education students generally display positive attitudes towards ICT integration, sustained progress depends on the establishment of robust, theory-driven institutional policies that promote equitable and sustainable use of technology. The study contributes to Sustainable Development Goal 4 (Quality Education) by promoting inclusive and equitable access to digital learning opportunities. It also aligns with SDG 9 (Industry, Innovation, and Infrastructure) through its emphasis on developing resilient ICT infrastructure and enhancing innovation capacity within higher education institutions. Recommendations include implementing mandatory computer literacy workshops, integrating ICTs strategically into curricula, and providing continuous professional development for staff.